2017
DOI: 10.1101/192740
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paternal-age-related de novo mutations and risk for five disorders

Abstract: BackgroundThere are well-established epidemiologic associations between advanced paternal age and increased offspring risk for several psychiatric and developmental disorders. These associations are commonly attributed to age-related de novo mutations. However, the actual magnitude of risk conferred by age-related de novo mutations in the male germline is unknown. Quantifying this risk would clarify the clinical and public health significance of delayed paternity.MethodsUsing results from large, parent-child t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Using spontaneous labor as a reference (no exposure to sOT), cases categorized as “fetal indication” for delivery (Table 1) as a group had significantly higher odds of ASD (OR = 2.00, 95% CI = 1.01–3.94, p = 0.044). To control for the possibility that fetal indications could confound the results in Tables 3 to 6, this variable was included as a covariate in subsequent analysis as was the presence of maternal hypertension (Curran et al, 2018), maternal diabetes (Li et al, 2016; OR = 2.04, p = 0.077), maternal education (as a substitute for the lack of socioeconomic status data), birth weight (Burstyn et al, 2010), maternal smoking (Caramaschi et al, 2018) or alcohol use during pregnancy (Bölte et al, 2019), the child’s race (Baio et al, 2018), and paternal age (Taylor et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Using spontaneous labor as a reference (no exposure to sOT), cases categorized as “fetal indication” for delivery (Table 1) as a group had significantly higher odds of ASD (OR = 2.00, 95% CI = 1.01–3.94, p = 0.044). To control for the possibility that fetal indications could confound the results in Tables 3 to 6, this variable was included as a covariate in subsequent analysis as was the presence of maternal hypertension (Curran et al, 2018), maternal diabetes (Li et al, 2016; OR = 2.04, p = 0.077), maternal education (as a substitute for the lack of socioeconomic status data), birth weight (Burstyn et al, 2010), maternal smoking (Caramaschi et al, 2018) or alcohol use during pregnancy (Bölte et al, 2019), the child’s race (Baio et al, 2018), and paternal age (Taylor et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The fact that aging is a large contributor to germline mutation has several implications for contemporary and historic populations. Children from parents of advanced age are more likely to suffer diseases caused by DNMs, such as intellectual disability, developmental disorders, autism, and epilepsy [4,39,[79][80][81]. In line with this, studies of historic populations indicated that late-born children on average have lower genetic fitness, as they were less likely to survive infancy and to engage in marriage [82][83][84].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 91%
“…10,[29][30][31] High paternal age is suggested to increase the risk of de novo variants in general. 32,33 We have not accounted for paternal age in our study, but this could be a topic for further investigations. The fact that the incidence of syndromic craniosynostosis was stable over the three time periods in addition to our calculation being based on very low numbers might indicate that this finding is a coincidence that should not be emphasized.…”
Section: Incidencementioning
confidence: 99%